Big Data-Driven Risk Analysis of Environmental Grievances in the Palm Oil Industry for Sustainable Decision-Making - Muhammad Syahmi Idris; Muhamad Shahrul Md Nor; Syazwani Ali; Norazman Mat Ali; Siew Wai Yoong; Mohd Nazli Mohd Nor; Mohd Suffian Mohd Muhili; Muhamad Fairus Noor Hassim (Jurnal Manajemen Hutan Tropika)
The expansion of the palm oil industry affects environmental sustainability. This study aims to assess palm oil's environmental grievances reported pre- and post-Covid-19. A hybrid of data-driven and multicriteria decision-making analyses was used to analyze unstructured data from nine companies' grievance logs. A total of 884 cases with the trend peaking in 2019. Predominantly deforestation, a total of 564 cases affecting ~66,716.23 ha in Indonesia, 312 cases affecting ~49,704.97 ha in Malaysia, 6 cases affecting ~43,500 ha in Papua New Guinea, and 2 cases in the Philippines. Network analysis reveals that the environmental grievances affected multiple companies, with WILMAR suppliers at the center. On average, companies take ~100 days to resolve. Clustering analysis shows Sime Darby Oil, WILMAR, KLK, and Mewah Group have influences on addressing grievances in high-risk provinces. Quantile-quadrant analysis reveals that provinces in Kalimantan, Pahang, and Sarawak are in the high-risk quadrant and therefore require immediate mitigation plans. This finding points toward the need for the formation of a private consortium among identified key players and local government in the high-risk region as a new strategy to improve management of environmental sustainability issues that predominantly involve deforestation.